Anthropometric profile, body composition and somatotype in elite traditional rowers: A cross-sectional study - León-Guereño, P.; Urdampilleta, A.; Zourdos, M. C.; Mielgo-Ayuso, J. (Revista Española de Nutrición Humana y Dietética, 2018)
Introduction: Given the importance of body composition in sports performance, it is vital to have references of elite athletes which serve as a guide when it comes to overseeing diet and training. The aim of this study was to describe the anthropometric values of an elite team of traditional rowers in order to build an anthropometric profile in this sport. Material and Methods: A cross-sectional design with twenty elite, male traditional rowers aged at 29.3 (3.6) years reported to the laboratory on a single day at the start of the competitive season. Height, wingspan, body mass, 8 skinfolds, 2 bone diameters and 6 perimeters were measured by the same internationally certified anthropometrist. Anthropometric measurements were taken following the International Society of Advancement of Kinanthropometry (ISAK) protocol. Fat mass was calculated using different equations for athletes and muscle mass using the Lee equation. For the somatotype components, the Carter and Heath equation was applied. Results: Elite traditional rowers had a wingspan of 189 (5.8) cm, body fat percentage of 8.0 (1.2)% (Carter), 8.0 (1.8)% (Withers), 7.0 (1.2)% (Yuhasz), and 10.9 (1.1)% (Faulkner). Muscle mass was 43.3 (2.4)% (Lee). The somatotype was endo-mesomorphic with endomorphy values of 3.5 (0.4), mesomorphy 4.7 (0.6) and ectomorphy 2.4 (3.5). Conclusions: These results suggest that wingspan seems to be of great importance for elite traditional rowers; while average height may not be as important for performance as wingspan. Meanwhile, reducing body fat percentage is likely to be beneficial in order to achieve elite rowingtatus.